Friendly Persuasion - West, Jessamyn (Harcourt, Brace, Wor, 1971)
A quintessential American heroine, Eliza Birdwell is a wonderful blend of would-be austerity, practicality, and gentle humor when it comes to keeping her faith and caring for her family and community. Her husband, Jess, shares Eliza's love of people and peaceful ways but, unlike Eliza, also displays a fondness for a fast horse and a lively tune. With their children, they must negotiate their way through a world that constantly confronts them-sometimes with candor, sometimes with violence-and tests the strength of their beliefs. Whether it's a gift parcel arriving on their doorstep or Confederate soldiers approaching their land, the Birdwells embrace life with emotion, conviction, and a love for one another that seems to conquer all.
Keywords: Family Life Fiction; Classic Literature & Fiction; American Literature